THE USE OF ACTIVE TEACHING METHODS IN ORDER TO IMPROVE THE EFFECTIVENESS OF EDUCATION - Mahmudova , Gulnora; Irgasheva , Dilrabo (MMIT Proceedings, 2023)
The article discusses the main trends in the development and improvement of the credit-modular system of education in higher education in Uzbekistan. The author draws attention to the main tasks and aspects of this system and problematic trends in its further improvement, the main ways to resolve them.